The Effect ofIslamic Religious Education on Religious Moderation Attitudes - Nurjamilah, Nurjamilah; Khairurrijal, Khairurrijal; Nasution, Syafri Martabe Rizka; Masyhudi, Fauza (Ahlussunnah: Journal of Islamic Education, 2025)
This study was conducted to determine the effect of Islamic religious education on the attitudes of moderation among students. This issue is based on the importance of teaching values of religious moderation, such as anti-violence, tolerance, commitment to nationality, fairness, self-confidence, and politeness. Schools, as the initial environment for character building, have a strategic role in internalizing these values to the younger generation. The objectives of this study are to determine the implementation of Islamic Religious Education in schools and to determine the effect of Islamic Religious Education on the attitudes of moderation among students. This study uses a quantitative method with an associative approach. The data collection technique for this research was in the form of distributing questionnaire instruments, then the data obtained was analyzed using simple linear regression through SPSS 25. The results of this study show that Islamic Religious Education has a strong positive impact on religious moderation attitudes, indicating that the variable of Islamic Religious Education contributes significantly to the formation of religious moderation, which includes aspects of tolerance, national commitment, anti-violence, fairness, confidence, and politeness. The implication is that Islamic Religious Education has a significant contribution in shaping moderate religious values among students. The next process with the T test produced a calculated T of 15.324, while the table T at a significance level of 5% was 1.708, so the calculated T > table T (15.324 > 1.708).  This indicates that there is a significant effect of Islamic Religious Education on the attitudes of moderation in religion among students